Testing The Effectiveness Of Cinnamon (Cinnamomumm Burmanni Blume) Ethanol Extract Against Salmonella Typhi Bacteria - Raja Quppar Siregar; Anggi Aprilyani (International Journal of Health and Pharmaceutical (IJHP), 2025)
Typhoid fever, caused by the bacterium Salmonella Typhi, remains a prevalent infectious disease with increasing antibiotic resistance posing a significant global health threat. This study aimed to investigate the in vitro antibacterial effectiveness of an ethanol extract from cinnamon bark (Cinnamomum burmannii) as a potential natural therapeutic alternative. The research employed a true experimental design with a post-test only control group. A pure culture of Salmonella Typhi was used as the sample. The cinnamon extract was prepared via maceration, and its antibacterial activity was evaluated using the standard Kirby-Bauer disk diffusion method. The inhibition zone diameters were measured and analyzed using non-parametric statistical tests, including Kruskal-Wallis and Mann-Whitney U tests. The results demonstrated that all concentrations (60%, 80%, and 100%) of the cinnamon extract exhibited strong antibacterial activity, with a dose-dependent inhibitory effect. Notably, the 100% extract concentration produced an inhibition zone diameter (15.57 mm) comparable to the positive control, chloramphenicol (15.66 mm). This study concludes that the ethanol extract of Cinnamomum burmannii is an effective antibacterial agent against Salmonella Typhi, providing a promising basis for developing natural therapies.